The Role of Organizational Commitment as a Predictor of Organizational Citizenship Behavior in Employees: A Literature Review - Muhammad Fikrie Hisram Aziz; Rahmawati Prihastuty (Universitas Negeri Semarang, 2025)
Organizational Citizenship Behavior (OCB) represents employees' voluntary work contributions that exceed formal job descriptions and are crucial for organizational effectiveness. However, its emergence is influenced by various factors. Organizational commitment, defined as employees' psychological bond with their organization, is believed to be a fundamental predictor of OCB. This research aims to comprehensively analyze the role of organizational commitment in fostering OCB among employees, addressing the research gap of existing inconsistent empirical findings. This study employs a Systematic Literature Review (SLR) approach guided by PRISMA. Data were collected from 20 national and international journal databases with a publication range of 2015-2025, using the keywords